1979
DOI: 10.1088/0031-8949/20/1/023
|View full text |Cite
|
Sign up to set email alerts
|

The Isomeric 9/2+and the Lowest 7/2-State in the Weakly Deformed N = 89 Nuclei

Abstract: The decays of the isomeric 9/2+ states which have been produced by (d, pγ) and (3He, xnγ) reactions, have been investigated in three N = 89 nuclei. The half-lives have been determined to be 5.1 ± 0.3 ns in 149Nd and 3.5 ± 0.4 μs in 153Gd. In 155Dy a 5.5 ns half-life was found, but we were unable to assign it to the 9/2+ state. The calculated E1 transition probability from the 9/2+ state has been used as a probe in suggesting the following main components for the lowest-lying 7/2- state: 7/2 5/2-[523] in 149Nd,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1982
1982
2004
2004

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 24 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Several of the N = 89 isotones were extensively studied [1][2][3][4]. In the A-~150 region, extensive systematic studies of long chains of isotones and isotopes have revealed the evolution of nuclear level structure from spherical to deformed nuclei.…”
Section: Introductionmentioning
confidence: 99%
“…Several of the N = 89 isotones were extensively studied [1][2][3][4]. In the A-~150 region, extensive systematic studies of long chains of isotones and isotopes have revealed the evolution of nuclear level structure from spherical to deformed nuclei.…”
Section: Introductionmentioning
confidence: 99%